Measuring, manipulating and exploiting behaviours of adult mosquitoes to optimize malaria vector control impact - Tusting, L; Killeen, G; Marshall, J; Kiware, S; South, A; Chaki, P; Govella, N (BMJ Publishing Group, 2017)
Residual malaria transmission can persist despite high coverage with effective long-lasting insecticidal nets (LLINs) and/or indoor residual spraying (IRS), because many vector mosquitoes evade them by feeding upon animals, feeding outdoors, resting outdoors, or rapidly exiting from houses after entering them. However, many of these behaviours that render vectors resilient to control with IRS and LLINs also make them vulnerable to some emerging new alternative interventions. Furthermore, vector control measures targeting preferred behaviours of mosquitoes often force them to express previously rare alternative behaviours, which can then be targeted with these complementary new interventions. For example, deployment of LLINs against vectors that historically fed predominantly indoors upon humans typically results in persisting transmission by residual populations that survive by feeding outdoors upon both humans and animals, where may then be targeted with vapour-phase insecticides and veterinary insecticides, respectively. So while the ability of mosquitoes to express alternative behaviours limits the impact of LLINs and IRS, it also creates measurable and unprecedented opportunities for deploying complementary additional approaches that would otherwise be ineffective. Now that more diverse vector control methods are finally becoming available, well-established entomological field techniques for surveying adult mosquito behaviours should be fully exploited by national malaria control programs, to rationally and adaptively map out new opportunities for their effective deployment.